2010
DOI: 10.1080/01425692.2010.484918
|View full text |Cite
|
Sign up to set email alerts
|

Young people, social capital and network‐based educational decision‐making

Abstract: This paper explores whether and in what ways young people's perceptions and experiences of higher education (HE) can facilitate the transmission within their social networks of social capital both upwardly (from child to parent) and horizontally (from sibling to sibling), and thus can potentially provide bridging capital to family members, especially in families with little or no prior experience of HE. It utilises data from a project that explored the embedded nature of decision-making about HE amongst a grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 18 publications
1
33
0
2
Order By: Relevance
“…Given the globalised labour market, social relationships with others with similar or different cultures may provide graduates with cultural capitals required to be successful in the long term. For example, studies by Heath, Fuller, and Johnston (2010) and Roth and Salikutluk (2012) confirmed that social networks may have an impact on attitude and perceptions towards education.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Given the globalised labour market, social relationships with others with similar or different cultures may provide graduates with cultural capitals required to be successful in the long term. For example, studies by Heath, Fuller, and Johnston (2010) and Roth and Salikutluk (2012) confirmed that social networks may have an impact on attitude and perceptions towards education.…”
Section: Introductionmentioning
confidence: 98%
“…First, embedded resources facilitate information flows between people, which consequently reduce the transaction costs, such as sharing of ideas, tasks or lessons learned. Second, social ties have a substantial influence upon how students deal with academic life and change in particular (Heath, Fuller, and Johnston 2010, Hommes et al 2012, Lee 2010. Third, social ties may be conceived as certification of social credentials, as it reflects a student's ability to access resources through social networks and relations.…”
Section: Social Capital Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Thus there is no unidirectional effect of parents on their offspring's educational pathways. As Heath, Fuller, and Johnston (2010) have shown, children are also able to convince their parents about the value of higher education if they attend university. Besides shaping the attitudes towards higher education, access to social capital also enhances the educational achievement of university students (Etcheverry, Clifton, & Roberts, 2001;Martin, 2009).…”
mentioning
confidence: 98%